Attitudes and Intention towards COVID-19 Vaccines among the Public Population in Mosul city - Rawee , Dr. Rawaa Y. Al-; Abdulghani , Mr. Mohammed Faris; Alsabea, Dr. Waleed Mohamed Basheer Yahya; Daoud, Dr. Mattie Amer; Tawfeeq, Dr. Bashar Abdul-Ghani; Saeed, Dr. Fadi Kamal (Jour Med Resh and Health Sci, 2021)
Aim: To assess the public’s response toward Vaccination in Mosul and causes of refusing vaccination and highlighting the need for an education program for vaccinations in Mosul city. Material and Method: Internet-based survey was completed among 1000 individuals residing in Nineveh. Google Forms is used for collecting data through an electronic questionnaire. Answer questionnaire lists starting with demographical information. The data were statistically analyzed by descriptive criteria for numerical variables using the number, percentage, mean and standard deviation. At the same time, for categorical variables, use frequency and percentages, Chi-square test, and independent t-test were used to test the significance of association between variables analyzed all by SPSS 25, and P-value was set at 0.5. Result: Significant associations of the vaccine agreement and the educational levels and working status of individuals (p-value 0.00118), Also significant association (P= < .00001) of the family history. Conclusion: Mosul’s residents have high-level agreement and willingness for a coronavirus vaccine. More education is needed to promote and ensure the community that the vaccine is efficient and secure.